Quiescence and Coral Biology: Will Warming Waters Result in a New Understanding on Coral Resiliency? - Grace, Sean P. (2018)
The objectives of this sabbatical were to examine the resilience of temperate corals (Astrangia poculata, Ellis & Solander 1787) and to address the following questions: 1. Do corals exhibit quiescence at warmer temperatures?; 2. Does Astrangia poculata exhibit quiescence across their geographic range?; 3. Does the microbial population on corals change during quiescence?; and 4. Does temperature cause a change in symbiotic state in A. poculata?
Keywords: dept.bio; faculty_collection; sabbatical_report